2024
DOI: 10.1159/000535916
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Treatment Guidelines in Ambulatory Heart Failure Patients with Reduced Ejection Fraction in a Latin-American Country: Observational Study of the Colombian Heart Failure Registry (RECOLFACA)

Alex Rivera-Toquica,
Luis Eduardo Echeverría,
Carlos Andrés Arias-Barrera
et al.

Abstract: <b><i>Introduction:</i></b> Although several guidelines recommend that patients with heart failure with reduced ejection fraction (HFrEF) be treated with angiotensin-converting enzyme inhibitors/angiotensin II receptor blockers (ACEIs/ARBs) or angiotensin receptor-neprilysin inhibitors (ARNIs), beta-blockers, mineralocorticoid receptor antagonists (MRAs), and sodium-glucose cotransporter-2 inhibitor (SGLT2i), there are still several gaps in their prescription and dosage in Colombia. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…In another article in this issue, Rivera-Toquica et al [4] used Colombian Heart Failure Registry (RECOLFACA) data to investigate compliance with GDMT in the treatment of HFrEF. They found that ACEIs or ARBs were prescribed to 72.3% of patients with HFrEF, β-blockers to 88.9%, MRAs to 67.9%, and ARNIs to 13.1%.…”
mentioning
confidence: 99%
“…In another article in this issue, Rivera-Toquica et al [4] used Colombian Heart Failure Registry (RECOLFACA) data to investigate compliance with GDMT in the treatment of HFrEF. They found that ACEIs or ARBs were prescribed to 72.3% of patients with HFrEF, β-blockers to 88.9%, MRAs to 67.9%, and ARNIs to 13.1%.…”
mentioning
confidence: 99%